2016
DOI: 10.1038/srep26159
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor 4D Fluorescence Microscopy using Ultrathin Bessel Light Sheets

Abstract: We demonstrate a simple and efficient method for producing ultrathin Bessel (‘non-diffracting’) light sheets of any color using a line-shaped beam and an annulus filter. With this robust and cost-effective technology, we obtained two-color, 3D images of biological samples with lateral/axial resolution of 250 nm/400 nm, and high-speed, 4D volume imaging of 20 μm sized live sample at 1 Hz temporal resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 15 publications
3
37
0
Order By: Relevance
“…In many previous publications a missing distinction between light sheet thickness and thickness of the main lobe could cause confusion, e.g. when referring to "ultrathin planar illumination produced by scanned Bessel beams" or "Ultrathin Bessel Light Sheets" when actually only the main lobe is thinner than a conventional Gaussian light-sheet of equal length [19,25]. For the most frequently used light sheet with a Gaussian profile there is only one sheet and the measure of main lobe thickness and light sheet thickness are strictly proportional.…”
Section: How Thick Is a Light Sheet? Main Lobe Thickness Vs Optical Smentioning
confidence: 99%
See 1 more Smart Citation
“…In many previous publications a missing distinction between light sheet thickness and thickness of the main lobe could cause confusion, e.g. when referring to "ultrathin planar illumination produced by scanned Bessel beams" or "Ultrathin Bessel Light Sheets" when actually only the main lobe is thinner than a conventional Gaussian light-sheet of equal length [19,25]. For the most frequently used light sheet with a Gaussian profile there is only one sheet and the measure of main lobe thickness and light sheet thickness are strictly proportional.…”
Section: How Thick Is a Light Sheet? Main Lobe Thickness Vs Optical Smentioning
confidence: 99%
“…Another way to understand the dithered lattice light sheet is based on the Field Synthesis Theorem [27]. The dithered light-sheet can also be understood as an incoherent superposition of three light sheets: a line Bessel sheet [19] and two Focused flat-top light sheets with poor confinement along the detection axis.…”
Section: Comparative Analysismentioning
confidence: 99%
“…As such it is of interest to look into nondiffracting, propagation‐invariant beams. Various reports have emerged over the past few years evaluating Bessel beams (Andilla et al, ; Fahrbach, Gurchenkov, Alessandri, Nassoy, & Rohrbach, ; Fahrbach & Rohrbach, ; Gao, Shao, Chen, & Betzig, ; Gohn‐Kreuz & Rohrbach, ; Zhang, Phipps, Goodwin, & Werner, ; Zhao et al, ) and Airy beams (Vettenburg et al, ) for LSFM, shown in Figure . Bessel beams are the most used as they are fairly easy to implement.…”
Section: Recent Technological Developmentsmentioning
confidence: 99%
“…Reportedly, a major advantage is the acquisition speed, that ranges between 200 to 1,000 planes/s in dithered mode, which is one order of magnitude more than with classic Bessel beams. The technique is undoubtedly very effective, but the set‐up is quite complex and the use of a SLM reduces the temporal resolution when multicolor imaging is required since the SLM must be rapidly switched and synchronized with every color change (Zhao et al, ). The solution proposed by Zhao and coworkers (Zhao et al, ) is to use a combination of “nonelectronic” optical components to create ultrathin Bessel sheets of the same thickness regardless of the input laser light, as long as it is in the visible range.…”
Section: Recent Technological Developmentsmentioning
confidence: 99%
See 1 more Smart Citation